2021
DOI: 10.51253/pafmj.v70isuppl-4.6005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Intravenous Versus Intr-Arterial Heparin for the Prevention of Radial Artery Occlusion During Transradial Coronary Artery Cathetherization

Abstract: Objective: To determine the relative efficacy of intravenous heparin as compared to intra-arterial heparin used during transradial coronary angiography for the prevention of radial artery occlusion. Study Design: Comparative cross-sectional study. Place and Duration of Study: Study was conducted at the Department of Cardiology, AFIC/NIHD Rawalpindi, Pakistan, from Jul 2019 to Dec 2019. Methodology: A total number of 144 patients were considered for the study using the consecutive sampling tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…13 Among various other factors, it has been reported that shorter duration of post procedure compression time and higher dose of anticoagulation can effectively lower the risk of radial artery occlusion. 14 A study conducted by Khalid W et al 15 compared intravenous vs. intra-arterial heparin use for the prevention of radial artery occlusion after coronary angiography.…”
Section: Discussionmentioning
confidence: 99%
“…13 Among various other factors, it has been reported that shorter duration of post procedure compression time and higher dose of anticoagulation can effectively lower the risk of radial artery occlusion. 14 A study conducted by Khalid W et al 15 compared intravenous vs. intra-arterial heparin use for the prevention of radial artery occlusion after coronary angiography.…”
Section: Discussionmentioning
confidence: 99%